Aerosol Optical Properties in the South Atlantic Ocean - Wilson, Dale (My University, 2012)
Atmospheric aerosols have direct and indirect impacts on the earth’s radiation budget and the radiative forcing on the climate system. A large uncertainty exists regarding aerosols and the effect they have on the earth’s radiation budget and global change. The distribution, concentration and types of aerosols are therefore of great importance regarding global warming and climate change. The purpose of this study is to present the atmospheric aerosol characteristics found over the South Atlantic, Southern Ocean and Antarctic continent as well as identify their origin. The aerosol optical properties over the South Atlantic and Southern Ocean region is analysed during the South African National Antarctic Expedition 2007/2008 (SANAE 47) take over cruise on board the M/V S.A. Agulhas. Very low aerosol optical thickness (AOT) values were obtained for the Antarctic Coastal region with a mean AOT500nm of 0.03 and a mean Angstrom exponent of 1.78. The South Atlantic region showed a mean AOT500nm of 0.06 and a mean Angstrom exponent of 0.72. AOT values for the South African coastal region had a mean AOT500nm of 0.07 and a mean Angstrom exponent of 0.76. Data comparisons confirm that the data acquired during the study are consistent with previous research from the study region. Comparisons were made between the dataset and the MODIS satellite aerosol product. A discrepancy was shown to exist between the MODIS aerosol product and the acquired dataset using the Microtops II Sunphotometer. Both MODIS TERRA and AQUA overestimate AOT at 550nm.
MSc., Faculty of Science, University of the Witwatersrand, 2011
Keywords: Aerosols; Aerosols (optical properties); Angstrom exponent; Aerosol optical properties; SANAE IV; South Atlantic; MODIS